2019
DOI: 10.18632/oncotarget.26908
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety analysis of immunotherapy combined with chemotherapy versus monotherapy in solid tumors: a meta-analysis of randomized clinical trials

Abstract: Background: Combination treatment (chemotherapy plus immune checkpoint blockade [ICB]) has shown promising activity in terms of efficacy, but it has been suggested that its toxicity profile is less favorable compared to monotherapy. Methods: We conducted a meta-analysis of published randomized clinical trials comparing combination treatment to monotherapy (chemotherapy or ICB) in patients with metastatic solid tumors. Differences in rates of safety issues (all-grade adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have demonstrated that the addition of chemotherapy to PD‐(L)1 inhibitors is a more effective option as a first‐line treatment for advanced NSCLC 17,18 . Meanwhile, adding chemotherapy might inhibit an overactive immune response and thereby reduce irAEs 3‐8,10,19‐28 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the addition of chemotherapy to PD‐(L)1 inhibitors is a more effective option as a first‐line treatment for advanced NSCLC 17,18 . Meanwhile, adding chemotherapy might inhibit an overactive immune response and thereby reduce irAEs 3‐8,10,19‐28 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Another study by Carretero-González et al, which involved 10 RCTs and 4,379 patients, revealed that the combination of immunotherapy with chemotherapy presented more grade 3/4 adverse events (RR: 1.32; 95% CI: 1.12-1.55) and discontinuations (RR: 2.31; 95% CI: 1.28-4.16). 15 Our study observed a significantly higher incidence of irEDs in patients treated with targeted+ICI compared with ICI-alone. The combination of targeted+ICI was also strongly associated with hypothyroidism using logistic regression.…”
Section: Discussionmentioning
confidence: 45%
“…However, the evaluation of PD-L1 remains mandatory for the administration of single agent pembrolizumab, especially as first-line treatment for those patients who are not eligible for chemotherapy. 25 , 26 The immunohistochemical assessment of PD-L1 has been validated in histological (biopsies and surgical specimens) and cytological samples treated as FFPE materials (pellets and clots). 12 19 , 21 However, in 20–30% of patients, the only available diagnostic material is a cytological smear, thereby precluding PD-L1 evaluation and pembrolizumab therapy.…”
Section: Discussionmentioning
confidence: 99%